2011
DOI: 10.1590/s0101-98802011000200002
|View full text |Cite
|
Sign up to set email alerts
|

Ressecções eletiva e de urgência para tratamento de neoplasia maligna do cólon em hospital universitário: estudo de 66 casos

Abstract: 120BORBA MR, BROCHADO MCRT, ALCÂNTARA PSM, LIMA TMA, ARANTES TS, OTOCH JP. Ressecções eletiva e de urgência para tratamento de neoplasia maligna do cólon em hospital universitário: estudo de 66 casos. Rev bras Coloproct, 2011;31(2): 120-125.Resumo: o câncer de cólon é uma doença de alta prevalência e mortalidade, cujo tratamento baseia-se na ressecção cirúrgica. A possibilidade de cura aumenta com o diagnóstico precoce, daí a importância dos programas de rastreamento populacional do câncer colorretal. o presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
2
2
1
2
Order By: Relevance
“…Unlike most of the studies showing a higher prevalence of colorectal neoplasms in male patients 18,19, our work has demonstrated that women composed almost half of the study population. This difference might be explained because the analysis was restricted to patients who underwent surgery in the emergency setting.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…Unlike most of the studies showing a higher prevalence of colorectal neoplasms in male patients 18,19, our work has demonstrated that women composed almost half of the study population. This difference might be explained because the analysis was restricted to patients who underwent surgery in the emergency setting.…”
Section: Discussioncontrasting
confidence: 98%
“…This difference might be explained because the analysis was restricted to patients who underwent surgery in the emergency setting. The same difference has been observed in other studies when analyzing a similar subset of patients 6,18,20,21.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As cirurgias realizadas em caráter de emergência apresentam um pior prognóstico quando comparadas com cirurgias eletivas 12,15,16,24,25,29 . Porém, a cirurgia de emergência não deve ser negada nem atrasada para pacientes oncológicos que necessitam de imediata intervenção, mesmo para aqueles com doença em atividade 21 .…”
Section: Discussionunclassified
“…Arrigoni et al 1 Obstrução aguda resolvida por recanalização endoscópica em 94% dos pacientes da série Borba et al 12 ; Hequera et al 13 Pacientes operados na urgência apresentaram estadiamento pT4 e os eletivos, estadiamento I Brochado et al 14 ; Porta et al 15 Pacientes com ressecção e anastomose primária, sem colostomia, taxa de mortalidade menor que os submetidos à ressecção com exteriorização, sem anastomose…”
Section: Principais Desfechosunclassified